Characterization of ZIIR element of BZLF1 promoter in the context of the whole Epstein - Barr Virus genome - Lim, Hui Jun (My University, 2007)
Latent infection of Epstein-Barr virus (EBV) is associated with many human cancers. Induction of lytic replication of EBV may lead to destruction of these tumor cells. The viral immediate-early gene, BZLF1, plays a key role in switching EBV infection from latent to lytic replication. Expression of the BZLF1 gene is down-regulated by a potent silencer element, ZIIR, located in the BZLF1 promoter (Zp). I introduced a 6-bp substitution mutation into the ZIIR element of Zp by mutagenesis of the genome of EBV strain B95.8, and studied the phenotype of this mutation in the context of the whole EBV genome. The human embryonic kidney cell line 293 was transfected with ZIIR mutant (ZIIRmt) EBV DNA, and independent clones of latently infected cells were grown out into cell lines. Strikingly, 293 cells latently infected with ZIIRmt spontaneously replicated EBV DNA and produced infectious virus, while cells latently infected with wild -type (WT) did not. Immunoblot analyses showed that ZIIRmt -infected 293 cells accumulated at least 30-fold more viral immediate-early proteins Zta and Rta and early protein BMRF1 than the WT-infected cells. Immunofluorescence staining confirmed the abundant presence of Zta, Rta, BMRF1 and viral late proteins gp125 and gp350 in ZIIRmt-infected cells, while these proteins were not detectable in WT-infected cells. Thus, the ZIIR element of Zp is crucial in the regulation of EBV's switch from latency to lytic replication.
32 p.
Keywords: Biochemistry; Genetics; Oncology